Makna Kafir dalam Al-Qur'an (Studi Komparatif Penafsiran Ibnu Kasir dan Quraish Shihab) - Ahmad Farhan; Deden Bagus Putra (El-Afkar: Jurnal Pemikiran Keislaman dan Tafsir Hadis, 2021)
The word infidel is mentioned 525 times in the Qur'an. The use of this word infidel has various meanings as in the QS. Ali 'Imran:151, the word infidels are those who associate partners with Allah while in QS. Luqman:12, the Qur'an calls the disbelievers those who disbelieve in the favors of Allah. The difference in the term infidel is not only limited to the verses of the Qur'an, but also applies among commentators, scholars, intellectuals, to ordinary people, including in the understanding of Indonesian society. This research is entitled "The Meaning of Kafir in the Qur'an (Comparative Study of the Interpretation of Ibn Kasir and M. Qurais Shihab)". In order to significantly answer the questions that arise; what is the meaning of infidel in the Qur'an according to Ibn Kasir in the book of Tafsir al-Qur'an al-'Azhim and M. Quraish Shihab in the book of Tafsir al-Misbah, similarities and differences in interpretation, and the relevance of their interpretation in the Indonesian context. This research is a library research that uses descriptive comparative analysis research method with a historical approach. The results of this study are: the socio-historical context, sources of interpretation, methods, and styles have a significant influence in producing differences in the interpretation of the Qur'an, especially regarding the meaning of kafir. Between Ibn Kasir and M. Quraish Shihab agreed to interpret the word infidel in the form of isim jama 'muzakkar salim (الكَافِرُوْنَ) in five (5) verses, namely QS. al-Mai'dah: 44, QS. al-A'raf: 45, QS. al-Taubah: 32, QS. al-Ankabut: 47, and QS. al-Rum: 8 with the meaning of denying and covering, but differing in explaining the interpretation of the five verses, although the difference is not that far away. The interpretations of the two figures in this thesis are very relevant to the context of Indonesia which is multi-religious and multi-cultural.